Analysis of The Influence of Human Resource Management on Innovation Mediated by Work Ethic in Government Office Employees West Sulawesi Province - K, Sakaria; Mattalatta, Mattalatta; Baharuddin, Baharuddin; Ilyas, Jamaluddin Bata; Ansar, Ansar; Kurniawaty, Kurniawaty (International Journal of Social Service and Research, 2023)
This finding provides an overview as a critical study to encourage the realization of human resource management for efforts to increase innovation mediated by excellent work ethic, so the research is intended to examine and analyze the influence of human resource management on innovation through work ethic both directly and indirectly. Data was collected through observation and questionnaires at the State Civil Apparatus at the West Sulawesi Provincial Government with a sample of 341 people. The data was analyzed with a quantitative approach, descriptive statistical data analysis techniques, and Structural Equation Model (SEM) analysis. This study found that human resource management positively and significantly influences work ethic. However, human resource management has a negative but insignificant effect on innovation. It was also found that work ethic has a positive and significant impact on innovation and that human resource management has a positive and significant effect on innovation when mediated by work ethic at the West Sulawesi Provincial Government office. The Regional Apparatus of West Sulawesi Province is expected to optimize human resource management to increase the quality of public service innovation provided to customers. It must be able to implement various dimensions of human resources management more optimally so that a more positive work ethic spirit will be realized, resulting in better public services. Innovation is a significant variable to be improved so that various innovation efforts will encourage learning public service products that increasingly provide comfort to the people who become customers. Therefore, it is necessary to strengthen the application of human resource management to foster the spirit of work ethic further and simplify innovation at the West Sulawesi Provincial Government Office so that public services can benefit the community more.